2021
DOI: 10.3102/0034654321995255
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionality Reduction in Exclusionary School Discipline: A Best-Evidence Synthesis

Abstract: A full canon of empirical literature shows that students who are African American, Latinx, or American Indian/Alaskan Native, and students who are male, diagnosed with disabilities, or from low socioeconomic backgrounds are more likely to experience exclusionary discipline practices in U.S. schools. Though there is a growing commitment to mitigating discipline disparities through alternative programming, it is clear that disproportionality in the application of harmful discipline practices persists. The purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 84 publications
2
30
1
Order By: Relevance
“…This is critically important considering the diversity of some Australian schools and the heterogeneity of cultures within them (Keddie et al, 2013). Recent results of a best-evidence synthesis investigating the effectiveness of school-based interventions in reducing disproportionality suggest, however that proscribing or banning the use of exclusionary discipline may be a critical first step to support meaningful change in both attitude and practice, which is a necessary foundation for successful reform implementation (Cruz et al, 2021).…”
Section: What Is Systemic Inclusive School Reform?mentioning
confidence: 99%
See 2 more Smart Citations
“…This is critically important considering the diversity of some Australian schools and the heterogeneity of cultures within them (Keddie et al, 2013). Recent results of a best-evidence synthesis investigating the effectiveness of school-based interventions in reducing disproportionality suggest, however that proscribing or banning the use of exclusionary discipline may be a critical first step to support meaningful change in both attitude and practice, which is a necessary foundation for successful reform implementation (Cruz et al, 2021).…”
Section: What Is Systemic Inclusive School Reform?mentioning
confidence: 99%
“…Beyond these adverse educational sequelae, disproportionate representation in school suspension and exclusion has been linked to overrepresentation in the criminal justice system (Hemez et al, 2020). Research evidence is particularly rich in relation to the criminalisation and incarceration of low-income African American, Latinx, and American Indian/Alaska Native children and young people (Cruz et al, 2021;Hirschfield, 2008), with exclusionary school discipline now considered a key contributor to a phenomenon described as the "school-toprison pipeline" (Novak, 2019). However, research investigating disproportionality in the use of exclusionary school discipline in settler colonies with a white non-indigenous majority outside of the United States-such as Australia, Canada, and New Zealand-is astonishingly rare, despite long documented evidence that indigenous (or First Nations) peoples are significantly overrepresented in these nations' criminal justice systems (Perdacher et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A resounding limitation in both discipline disparities research and special education disproportionality research is a lack of theoretical framing (Cruz et al, 2021; Kulkarni, 2017; Sullivan & Artiles, 2011). Thus, we use a theoretical framework that bridges the divide between quantitative studies that seek to explain disproportionality (see Cruz & Rodl, 2018a; Morgan et al, 2017) and qualitative works that center the voices of those who experience racism, ableism, exclusion, and erasure within sociological systems (see Harry & Fenton, 2016).…”
Section: Interrogating Special Education and Discipline Disparities Through Discrit And Quantcritmentioning
confidence: 99%
“…Although federal and state agencies have identified racial disproportionality in both special education placement and exclusionary discipline enactment as a significant problem, research has presented inconsistent findings regarding causes of disproportionality in special education (see Morgan & Farkas, 2016; Skiba et al, 2016), and studies related to reduction of discipline disparities remain scant (see Cruz et al, 2021). Furthermore, Cruz et al found that studies of school-based programs meant to reduce discipline disparities have rarely focused on the intersecting forms of oppression, exclusion, and erasure (see Annamma et al, 2018; Blake et al, 2017) that cause multiply marginalized students (i.e., those who experience multiple and intersecting oppressions in schools) to experience these exclusionary outcomes at higher rates.…”
mentioning
confidence: 99%